Clinical Safety and Efficacy of Hyaluronic Acid–Niacinamide–Tranexamic Acid Injectable Hydrogel for Multifactorial Facial Skin Quality Enhancement with Dark Skin Lightening - Sarah Hsin; Kelly Lourenço; Alexandre Porcello; Michèle Chemali; Cíntia Marques; Wassim Raffoul; Marco Cerrano; Lee Ann Applegate; Alexis E. Laurent (Gels)
Facial aging is a complex process manifesting as skin hyperpigmentation, textural irregularities, and a diminished elasticity, hydration, and evenness of tone. The escalating demand for minimally invasive aesthetic interventions has driven the development of advanced hydrogel-based injectable formulations. This clinical study assessed the safety and efficacy of Hydragel A1, an injectable hydrogel containing hyaluronic acid (HA), niacinamide, and tranexamic acid (TXA), designed to simultaneously address multiple facets of facial skin aging. A cohort of 49 female participants underwent a series of objective and subjective assessments, including the Global Aesthetic Improvement Scale (GAIS), instrumental measurements (Antera 3D, Chromameter, Cutometer, Dermascan, Corneometer), and standardized photographic documentation at baseline (Day 0) and 14, 28, and 70 days post-treatment. The results demonstrated statistically significant improvements in skin hydration, texture, elasticity, and pigmentation following Hydragel A1 administration. Notably, no serious adverse events or significant injection site reactions were observed, confirming the favorable safety profile of the investigated device. Collectively, these findings underscore the potential of a combined HA, niacinamide, and TXA injectable formulation to provide a comprehensive approach to facial skin rejuvenation, effectively targeting multiple aging-related mechanisms.